1990
DOI: 10.1007/bf01857639
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac effects of angiotensin converting enzyme inhibitors

Abstract: ACE inhibitors have provided a major advance in cardiovascular therapeutics. The rationale for their use in hypertension and heart failure, and their cardiac effects are well documented. Further information is required on the relevance of their direct myocardial and other tissue effects, and it is likely that their use in hypertension and heart failure will increase further over the next several years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Experimental and clinical studies have suggested that ACE inhibitors may also prevent the occurrence of ischaemic heart disease and exert cardioprotection following acute myocardial infarction (Pfeffer et al 1985;Sharpe 1990). So far, there is no epidemiological evidence that these drugs decrease the incidence of coronary heart disease.…”
Section: Indications For Usementioning
confidence: 98%
See 1 more Smart Citation
“…Experimental and clinical studies have suggested that ACE inhibitors may also prevent the occurrence of ischaemic heart disease and exert cardioprotection following acute myocardial infarction (Pfeffer et al 1985;Sharpe 1990). So far, there is no epidemiological evidence that these drugs decrease the incidence of coronary heart disease.…”
Section: Indications For Usementioning
confidence: 98%
“…Any primary protection with these agents could theoretically be related to the fact that they decrease blood pressure, do not affect lipid metabolism and may improve insulin sensitivity and cause regression of left ventricular hypertrophy. With regard to secondary protection, ACE inhibition is associated with an increase in coronary blood flow and antianginal effects in patients with symptomatic coronary insufficiency (Sharpe 1990).…”
Section: Indications For Usementioning
confidence: 99%
“…In addition to reducing the preload and afterload (92), an inhibitory effect of ACE inhibitors on the cardiac renin-angiotensin system (20) was suggested to be a contributing factor.…”
Section: Congestive Heart Failurementioning
confidence: 98%
“…ACE inhibitors became first-line drugs for the treatment of CHF because of the favorable results from large-scale prospective studies such as the SOLVD study (109) and the VHeFT-II study (12). In addition to reducing the preload and afterload (92), an inhibitory effect of ACE inhibitors on the cardiac renin-angiotensin system (20) was suggested to be a contributing factor.…”
Section: Congestive Heart Failurementioning
confidence: 99%